Ultrasound-Guided Pleural Access - Shojaee, Samira; Argento, A. Christine (Seminars in Respiratory and Critical Care Medicine, 2014)
Ultrasonography of the thorax has become a more recognized tool in pulmonary medicine, thanks to continuing clinical research that has proven its many valuable roles in the day-to-day management of pulmonary and pleural diseases. Ultrasound examination is a cost-effective imaging modality that permits the pulmonologist to obtain information about the pathologies in the thorax without the risk of exposure to ionizing radiation, providing the examiner with real-time and immediate results. Its ease of use and training along with its portability to the patient's bedside and accurate examination of the pleural space has allowed for safer pleural procedures such as thoracentesis, chest tube placement, tunneled pleural catheter placement, and medical thoracoscopy. In this review, we summarize the technique of chest ultrasonography, compare ultrasound to other frequently used thoracic imaging modalities, and focus on its use in obtaining pleural access while performing invasive pleural procedures.
Keywords: ultrasound; pleural effusion; thoracentesis; thoracic ultrasonography; pleural disease; pneumothorax; chest tube